Effectiveness of an Education Program on Nursing Staffs' Knowledge about Infection Control Measures at Intensive Care Unit in Al-Diwaniya Teaching Hospital - Rajih, Qasim; mohammed, widad (Iraqi National Journal of Nursing Specialties, 2020)
Objectives: To determine the effectiveness of the educational program on nursing staff knowledge about infection control measures at the Intensive Care Unit in Al-Diwaniya Teaching Hospital.Methodology: A pre-experimental design (one group design: pre-test and post-test) was used. This study was conducted in Al-Diwaniya Teaching Hospital for the period from ( 20th February to 5th March, 2020) on a non-probability (purposive) sample consisting of (25 nurses) working in ICU. A questionnaire was built as a data collection tool and consisted of two parts:First part: The demographic characteristics of the nursing staff (age, gender, level of education, years of experience in nursing, years of experience in ICU, participation in training courses related to infection control measures, and marital status).Second part: Evaluation of the nursing staff knowledge about infection control measures in ICU, which consist of (39) multiple-choice questions. The validity of the questionnaire and the educational program were verified by presenting it to (11) experts. The sample has received a pre-test, educational program, and post-test. Descriptive and inferential statistics were used to analyze the results of the study using the Statistical Package of Social Sciences (SPSS) version 25 and Microsoft Excel (2010).Results: The study finding shows, that all the study sample responses at the pre-test were fair knowledge with a statistical mean of scores (1.342). Other than the post-test, shows (100%) of the study sample has high knowledge at the mean of scores (1.879). Also, the results revealed a highly significant difference between the pre-test and post-test of the study sample after participated in the educational program at the p-value (0.0001). The researcher concluded that the educational program was effective in the enhancement of nursing staff knowledge about infection control measures in ICU.Recommendations: The study recommended the necessity of activating the role of continuing medical education correctly in order to give courses about infection control measures for all health care workers, as well as activate the national infection control program in Iraqi health facilities (2009).